Optimalisasi Pengembangan UMKM “Kiara Snack” Melalui Pendampingan Digital Marketing Dan Branding Di Desa Musir Lor, Kecamatan Rejoso, Kabupaten Nganjuk - Widyana Dini Maylinda; R. Yuniardi Rusdianto (Universitas Katolik Widya Karya Malang, 2023)
The growth of businesses on a micro, small and medium scale is in line with technological advances that are also experiencing rapid development. The Internet is one of the technological advancements that can be used for online product marketing, either through social media or e-commerce. Digital marketing and branding are the right marketing and media strategies to reach a wider market. This digital marketing and branding assistance activity aims to educate and facilitate MSMEs in Musir Lor Village to reach their consumers globally. Using the ABCD method through an approach that focuses on assets owned by MSMEs, this devotion activity seeks the realization of a social life order so that people can become perpetrators and determine development efforts in their environment. This assistance activity uses an object, namely MSME